A methodological overview to defining and measuring "digital" financial literacy. Issue 2 (9th June 2021) - Lyons, Angela C.; Kass‐Hanna, Josephine
Abstract: Researchers and financial practitioners alike recognize the importance of defining and measuring financial literacy (FL) to better understand its relationship to financial behavior and decision‐making. Despite many efforts, there is still no widely accepted definition or methodological approach for measuring FL. The rapid expansion of digital financial services (DFS), which promises to enhance financial inclusion and improve personal financial management, has brought to light a new challenge: linking FL to digital literacy (DL) and assessing their dual effect on financial outcomes. Recent research has even proposed a framework to operationalize the emerging concept of digital financial literacy (DFL), as traditional FL definitions and metrics have become insufficient to capture the specificities of financial services within a digital context. This survey article discusses empirical research techniques being used to assess FL, DL, and most recently DFL. It highlights the characteristics and limitations of these approaches and suggests ways to address some of the challenges related to the construction, testing, weighting, and standardization of multidimensional measures, as well as methodological issues related to modeling and estimation. The article is a helpful guide to researchers and practitioners interested in FL in general and in the emerging concept of "digital" financial literacy.